2013
DOI: 10.1016/j.molcel.2013.07.020
|View full text |Cite
|
Sign up to set email alerts
|

The Origin of B Cell Recurrent Chromosomal Translocations: Proximity versus DNA Damage

Abstract: B cell lymphomas are characterized by recurrent chromosomal translocations. Why these events are so prevalent is an area of active investigation. Several ideas have been put forward to try to explain this phenomenon, including: nuclear proximity between translocating genes; repeated DNA damage by enzymes that mediate Ig gene recombination (AID and RAGs); and selection for deregulated oncogenes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…There is no evidence in human lymphoid translocations that proximity is an important factor. Rather, the DNA breakage process appears to be the rate-limiting step, and studies in murine systems support this interpretation 83 .…”
Section: Future Questionsmentioning
confidence: 99%
“…There is no evidence in human lymphoid translocations that proximity is an important factor. Rather, the DNA breakage process appears to be the rate-limiting step, and studies in murine systems support this interpretation 83 .…”
Section: Future Questionsmentioning
confidence: 99%
“…However, 4C analysis by the Skok group of the Igh gene came to the opposite conclusion; they found that a very strong correlation exists between the genes that coassociate with Igh in normal cells and those that have a predisposition to translocate (42). The differences are being hotly debated and largely relate to how the bioinformatics analyses have been carried out (43,44). Input from other bioinformaticians with expertize in genome organization and handling such datasets would be highly beneficial to help resolve these differences of interpretation.…”
Section: Proximity Transcription and Chromosomal Translocationsmentioning
confidence: 99%
“…Off-target activity of the diversification enzymes may provide the initial step in the translocation process through the formation of DNA double-strand breaks in genes spatially proximal to IGH (Peters and Storb, 1996;Fukita et al, 1998;Pasqualucci et al, 2001;Schrader et al, 2007;Liu et al, 2008;Robbiani et al, 2008;Tsai et al, 2008;Hu et al, 2015). Casellas et al suggest that the translocation frequency of AID targets is determined by the amount of enzyme-mediated DNA damage, and although necessary, not predicted by proximity to IGH (Casellas et al, 2013).…”
Section: Discussionmentioning
confidence: 99%